Measuring the effect of Users' Privacy Concerns on the Use of Jakarta Smart City Mobile Application (JAKI) - Arif Wahyudi; Mirza Triyuna Putra; Dana Indra Sensuse; Sofian Lusa; Prasetyo Adi; Assaf Arief (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Jakarta Kini (JAKI) is a super-app developed by Jakarta Smart City that offers a one-stop service to help citizens connect and communicate with the Government. It is undeniable that the use of mobile applications can indeed facilitate people's activities, but on the other hand, it also poses risks and raises concerns in terms of privacy. The purpose of this study is to assess the impact of users' privacy concerns on their tendency to use the JAKI mobile application. To measure the privacy concern, we conduct an online survey of the users of JAKI. The hypothesis and research model were formulated to assess the users' privacy concerns based on the Mobile Users' Information Privacy Concerns (MUIPC) theory, with additional factors, namely prior privacy experience and awareness, as the antecedents. As a result, we found that MUIPC had a significant effect on negatively influencing the intention to use the JAKI application. Our study contributes as a starting point in exploring privacy research in the context of a smart city in Indonesia. Additionally, this study proved that the IPC scales that were originally designed for English-based countries could also be adapted to Bahasa Indonesia and utilized in the Indonesian context.